MOTIVASI KERJASAMA INDONESIA-MALAYSIA DALAM INVESTASI PENERBANGAN MASKAPAI AIRASIA - Feni Cikita; Syafri Harto (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Geographical conditions that shaped the Islands causing air transportation became one of the main transport in the country. The function of air transport is very important given the domestic flight can reach the entire city in Indonesia, especially when land and sea transportation cannot reach it.Characterize AirAsia's competitive strategy with a focus on low-cost carriers, or low cost carrier (LCC). Segments that are served, especially those who are price sensitive, even a layer of society that has never used air transportation is able to boost the existence of this flight. AirAsia can attract media attention with those low cost airlines, and it also attracts customers. In addition AirAsia also has many routes, both domestic and InternationalKeyword : AirAsia Airlines, Strategy, Low Cost Carier (LCC), Investment